Implementation of Family Centered Care for Neonates Admitted in a Special Care Baby Unit in Sierra Leone - Johnson JO (Dove Medical Press, 2024)
Jedidah Olayinka Johnson Department of Pediatrics, University of Sierra Leone Teaching Hospital Complex, Freetown, Sierra LeoneCorrespondence: Jedidah Olayinka Johnson, Department of Pediatrics, University of Sierra Leone Teaching Hospital Complex, Freetown, Sierra Leone, Tel +232 79533962, Email jedidahj18@gmail.comPurpose: To assess the feasibility of implementing family centered care and the impact this would have on parental satisfaction in a special care baby unit in Sierra Leone.Patients and Methods: A cross-sectional, mixed methods study was conducted at the Rokupa Government Hospital, Sierra Leone. 16 nursing staff of the Special Care Baby Unit and 7 caregivers of neonates admitted in the unit participated in the study. Quantitative data on feasibility was obtained from nursing staff using a five-point Likert scale administered to staff before and after implementation of family centered care in the unit. Qualitative data on perception of impact was obtained through focus group discussions for caregivers whose neonates had received family centered care and a control group who had received standard unit care. Quantitative data was analyzed using univariate analysis and thematic analysis was undertaken for qualitative data.Results: Before implementation, most nursing staff felt implementation of family centred care was not feasible (87.5%) and more than half of nursing staff either strongly agreed or agreed with each of the negative statements regarding the practice of family centred care indicating a generally negative perception. After implementation there was improvement in nursing staff perception of family centred care, however the majority still doubted the continued feasibility of this practice (68.8%). Qualitative discussions with caregivers demonstrated that caregivers whose babies received family centered care were less distressed and more satisfied during the period of admission than those who received routine care.Conclusion: Family centered care improved the experiences of caregivers in the unit. Nursing staff also demonstrated a better understanding of the benefits of family centered care after it was implemented. Concerns regarding understaffing and the unit being too small to accommodate caregivers and staff at the same time need to be addressed. There is need to integrate family centered care into hospital policy.Keywords: family centered care, neonates, nursing care, Sierra Leone